The Principle of Al-Wahid: The Foundation of the Unity of Existence in Islamic Philosophy - Kholid Al Walid; Rosmaria Sjafariah Widjajanti (Aqlania, 2025)
The Principle of Al-Wahid serves as a foundational concept in Islamic philosophy, asserting the oneness of reality and that all existence originates from a single, unified source. Diversity does not stem from multiple origins but rather from the varying degrees of distance that levels of existence have from the Absolute Source of Being. This absoluteness negates the possibility of plurality within the Primary Cause itself. The principle has been a subject of discourse since the early history of Islamic philosophy, although some philosophers trace its roots back to Greek philosophy. This study employs a library research methodology with a Burhani (rational-analytical) approach. The findings of this research demonstrate that existence is fundamentally one; plurality arises not from multiple causes, but from the weakness of the effects, which leads to various limitations and, consequently, plurality. The study confirms that the principle of Al-Wahid is rational, supported by strong arguments, and serves as evidence for the most fundamental Islamic principle, al-Tawhid.